Experimental analysis of seismic torsional ground motion recorded by the LSST Lotung array. - Laouami, Nasser (Earthquake engineering & structural dynamics.)
The purpose of this study was to perform an experimental analysis of the amplitude of full scale spatial variability of seismic motions with regard to earthquake engineering. The LSST Lotung array in Taiwan provides a good set of records for this type of study. Of interest are the free field torsional seismic components induced by the spatial variability of seismic motions. In this study, three events have been considered : LSST-06, LSST-07 and LSST 16. In time domain analysis, the experimental results obtained show that when the separation distance increases, the induced torsion decreases, and the normalized differential motion parameter increases. Also, the results show that the stronger the event, in terms of maximum PGA, the larger the induced torsional amplitude and the smaller the induced normalized differential motion parameter.